1992
DOI: 10.1111/j.1432-1033.1992.tb17197.x
|View full text |Cite
|
Sign up to set email alerts
|

Point mutation in cytochrome b of yeast ubihydroquinone:cytochrome‐c oxidoreductase causing myxothiazol resistance and facilitated dissociation of the iron‐sulfur subunit

Abstract: Cytochrome-c reductase was isolated from Succhuromyces cerevisiue GM50-3C. A tenth subunit was detected with molecular mass 8.5 kDa on SDSIPAGE.Two yeast mutants selected for resistance to myxothiazol, an inhibitor of the Qo center (Q.ubiquinone) of cytochrome-c reductase, were analysed. The single amino acid substitution in the cytochrome-b subunit, N256Y in the mutant Myx-119 and G137R in the mutant Myx-118, caused a general resistance to all methoxyacrylate inhibitors to about fivefold higher concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Mitochondria1 membranes were isolated according to Geier et al [21], frozen rapidly in liquid nitrogen and stored at -80°C. The mitochondrial membranes were diluted to approximately 20 mg/ml protein in 1.1 % Triton X-100, 200 mM NaCl, 5 mM EDTA, 1 mM phenylmethylsulfonyl fluoride (PhMeSO,F), 10 mh4 potassium phosphate, pH 7.2, and centrifuged for l h at 100000 g. Complexes I11 and IV of the mitochondrial respiratory chain were extracted with 2.2% Triton X-100, 600 mM NaC1, 5 mM EDTA, 1 mM PhMeSO,F, 10 mM potassium phosphate, pH 7.2.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria1 membranes were isolated according to Geier et al [21], frozen rapidly in liquid nitrogen and stored at -80°C. The mitochondrial membranes were diluted to approximately 20 mg/ml protein in 1.1 % Triton X-100, 200 mM NaCl, 5 mM EDTA, 1 mM phenylmethylsulfonyl fluoride (PhMeSO,F), 10 mh4 potassium phosphate, pH 7.2, and centrifuged for l h at 100000 g. Complexes I11 and IV of the mitochondrial respiratory chain were extracted with 2.2% Triton X-100, 600 mM NaC1, 5 mM EDTA, 1 mM PhMeSO,F, 10 mM potassium phosphate, pH 7.2.…”
Section: Methodsmentioning
confidence: 99%
“…These results support the speculation that the driving force for the movement of the reduced head domain of ISP is the molecular event of electron transfer from b L to b H during the catalytic cycle. It should be mentioned that the redox state dependent binding of stigmatellin or MOAS to the cytochrome bc 1 complex has been investigated by several laboratories [23][24][25][26][27]. A relative wide range of binding or dissociation constants has been obtained with different explanations.…”
Section: Introductionmentioning
confidence: 99%
“…The side chain of Phe 129 is in hydrophobic interaction with the tail of stigmatellin and probably with that of the substrate. This residue is a locus of center P inhibitor resistance both in yeast and bacterial QCR (17)(18)(19). Mutational analysis of the equivalent residue in bacterial QCR (Phe 144 ) indicated that replacement of Phe 144 affects ubiquinol binding and oxidation (9).…”
Section: /Ementioning
confidence: 99%